La gestión del conocimiento y su relación con la gestión de la calidad, en instituciones del sector agropecuario dedicadas a la ciencia y la tecnología (2011)
The current moment is considered a time change, called the time of knowledge and information. Traditional resource generators of value such as the earth and the financial capital are not the engines of economy anymore and they are being replaced by a new value generating resource: information and knowledge. The new sources of competitiveness and of wealth creation must be managed in the organizations based on knowledge.In Colombia the science and technology entities in the agricultural sector although starting to implement quality and excellence management systems are still producing little progress in knowledge management.This research studies, in two institutions of the agricultural sector devoted to science and technology, the Instituto de Investigación Agropecuaria – ICA (Institute of Agricultural Research) and the Corporación Colombiana de Investigación Agropecuaria – CORPOICA (Colombian Corporation of Agricultural Research), that have quality management systems implemented, what congruencies, affinities or inconsistencies can be found in their management systems and the knowledge management elements identifying when tackling some categories such as intellectual capital, knowledge flow, learning culture, innovation culture and continuous improvement.On the basis of a critical analysis of the theoretical frame, a Category Matrix is prepared as a result of the identification of key concepts converted into categories, and which are found in different approaches and models of knowledge management and of quality management. Once the information obtained through the application of instruments is analyzed, the research concludes that there are knowledge management features in the agricultural research organizations, which makes it possible to verify the hypothesis provided that states that quality management, through the establishment of Management Systems or Models can be the basis for the integration of knowledge management in the agricultural research organizations.